อัตลักษณ์การสร้างสรรค์ตัวละครในวรรณกรรมเรื่องสั้นของทัศนาวดี Identity on character creation in short stories of Thassanawadee - วงศ์กระบากถาวร สุทัศน์; ศรยาภัย วรวรรธน์ (Chophayom Journal, 2017)
บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อวิเคราะห์อัตลักษณ์การสร้างสรรค์ตัวละครในวรรณกรรมเรื่องสั้นของทัศนาวดี ในด้านกลวิธีการสร้างตัวละคร การนำเสนอ และแรงจูงใจในการแสดงบทบาทของตัวละคร ข้อมูลที่ใช้ในการวิเคราะห์ ได้แก่ รวมเรื่องสั้นของทัศนาวดี 7 ชุด จำนวน 63 เรื่อง ผลการวิเคราะห์พบว่า ตัวละครที่ผู้เขียนสร้างสรรค์ขึ้นมี 4 ลักษณะ ได้แก่ ตัวละครที่มีพฤติกรรมดี, ตัวละครเปลี่ยนพฤติกรรมจากดีเป็นร้าย, ตัวละครที่มีพฤติกรรมร้าย, ตัวละครเปลี่ยนพฤติกรรมจากร้ายเป็นดี ตัวละครในเรื่องสั้นสร้างจากจินตนาการ, ข้อเท็จจริง, ข่าวเหตุการณ์ ผู้เขียนนำเสนอตัวละครโดยตรงและโดยอ้อม และบทบาทของตัวละครเกิดจากแรงจูงใจภายในและแรงจูงใจภายนอก คำสำคัญ : อัตลักษณ์การสร้างสรรค์, วรรณกรรมเรื่องสั้น, ทัศนาวดี ABSTRACT This article aims to analyze the identity of character creation in short stories written by Thassanawadee in order to exhibit strategies in creating characters, presentation and motivation in role performance of those characters. The data used in the analysis includes the seven series of the short stories written by Thassanawadee which consist of 63 stories. The results of the analysis indicated that the characters created by the author have four characteristics in order as follows; 1) good characters 2) good to bad characters 3) bad characters 4) bad to good characters. All characters in the short stories concerned were found that they were created from imagination, facts and news stories The author presented the characters with direct references and with indirect references. In this regard, the roles of the characters were created from the author’s internal motivation and external motivation. Keywords : Identity in creating, Short Story, Thasanswadee